Personal Educational Actions Management for Students at the Stage of Primary General Education - USMANOVA, SOFIA G.; MALOLETKOVA, ANNA V.; SAYFULLINA, GUZEL F.; GAZIZOVA, REGINA R.; SEDOVA, SVETLANA B. (The journal of contemporary issues in business and government, 2021)
Background: The ongoing transformation of Russian society determines the requirements for a person, an active member of a new society. They must have a different motivation, a new style of behavior, qualitatively different thinking, which will allow them to work actively and live in new social relations. Based on this, new tasks are set for the education system, requiring a revision of the current goals and values of the educational system. The education system modernization is taking place, among other things, through the introduction of Federal State Educational Standards (or FSES). The FSES of the second generation states that its purpose is to determine and ensure the achievement of the requirements and conditions that are put forward by the state, aimed at the implementation of the main goal of the Russian educational system is the upbringing of a successful person, a citizen of a high level of morality, possessing modern knowledge, skills, and abilities, and respecting social ideals and values. FSES of the second generation has a fundamental difference from previously implemented educational standards. It is based not only on the achievement of given subject results but on the formation of universal methods of educational activity in students, which determine the success of the child’s learning in the future at all educational stages. The new educational standard is based on the idea of the relationship and interdependence of the processes of education, training, and personal development. Seeing this, the goal of modern education is to shape the personality of the child. Objective: based on theoretical and empirical research results, the aim is to develop, substantiate and test a program for managing the development of personal educational universal actions in younger schoolchildren. Methods: theoretical: analysis, generalization, comparison, systematization; empirical: pedagogical observation, pedagogical experiment, testing, methods of mathematical and statistical processing, and data interpretation. Findings: the characteristics of the personal development of junior schoolchildren are characterized; describes the goals and objectives of managing the personal development of students in the implementation of the federal state educational standard of primary general education; theoretically substantiated and characterized by a program for managing the formation of personal universal educational actions of primary schoolchildren. The developed program can be used by psychologists and teachers to organize work to manage the formation of personal universal educational actions of students at the stage of primary general education. The materials can be used by teachers and students in the process of preparing for lectures and practical classes. Conclusion: students at the stage of primary general education have an insufficient level of development of personal universal educational actions. Program-targeted management of the process of forming personal universal educational actions of primary schoolchildren will ensure its effectiveness and efficiency.